Development of the Ideas of the Activity Approach to the Preschool Education in Ukraine in the Late XIX – Early XX Century: Historiography and Source Materials Research - Sichkar, Alla (Pedagogical Discourse, 2013)
The main groups of historical and educational sources to examine and summarize the material on the issue of the development of the ideas of activity approach in pre-school education in Ukraine at the end of XIX – early XX century is identified and described in the article. Based on the analysis of historiographical research and study of the source base, the ideas of the activity approach, their development in domestic and foreign pedagogy, especially the organization of the practice of early childhood education in a view of the natural needs of the child in the activity are defined. The choice of the theme of our research is determined by the fact that activity approach is one of the fundamental modern educational principles in preschool education in Ukraine.